PROFESSIONAL EXAMINATIONS A Department for Students of Accounting. - Chamberlain, Henry T. (The Accounting Review, 1946)
The following problems were prepared by the Board of Examiners of the American Institute of Accountants and were presented as the second half of the Certified Public Accountant (CPA)examination in accounting practice on November 8, 1945. One of the questions asked was to prepare a consolidated balance-sheet of Holding Co. and its wholly-owned subsidiary as at July 31, 1944. The response to this began as; on June 30, 1944, A &Co;, partnership (profits and losses shared equally), and X Corp. consummated a consolidation agreement pursuant to the terms of which Consolidated Co., newly organized and incorporated with an authorized capital of 20,000 shares of $100 par value common stock, acquired for its common stock issued in the amount of $950,000 to A &Co; and $550,000 to X Corp. certain net assets of the companies. A &Co; All net assets (including buildings at an appraised sound value of $1,100,000), excluding notes payable X Corp. All net assets excluding buildings. The article includes the balance sheet as response to the question.